A pilot study of virtual reality as an alternative to pharmacological sedation during colonoscopy - Friedman, Madeline; Rand, Kyle; Patel, Tobias; Colizzo, Francis; Carolan, Peter; Kelsey, Peter; Chung, Daniel C. (Endoscopy International Open, 2021)
Background and study aims Conscious sedation is routinely administered for colonoscopy but is associated with risks and inconveniences. We sought to determine whether virtual reality (VR) may be a feasible alternative.Patients and methods Twenty-seven individuals scheduled for screening/surveillance colonoscopy participated. The VR device was activated throughout the colonoscopy, but subjects could opt out and request standard medications. Questionnaires were administered, and variables were assessed on a scale of 1 to 10.Results Cecal intubation was achieved in all cases without adverse events (AEs). Study colonoscopies were completed without pharmacological rescue in 26 of 27 patients (96.3 %) and procedure times were comparable to baseline. Subjects reported minimal pain, high satisfaction, and willingness to use VR for future colonoscopies to avoid narcotics and resume normal activities including driving.Conclusion Replacing pharmacological sedation with VR did not impact colonoscopy completion rates, procedure time, or AEs. Satisfaction was high and only one subject (3.7 %) chose to suspend VR. VR can be an effective alternative for patients undergoing colonoscopy who prefer to avoid narcotics.